Nudix Hydroxylase 15 Mutations Strongly Predict Thiopurine-Induced Leukopenia Across Different Asian Ethnicities: Implications for Screening in a Diverse Population - Khoo, Xin-Hui; Wong, Shin Yee; Ibrahim, Nik Razima Wan; Ng, Ruey Terng; Chew, Kee Seang; Lee, Way Seah; Wong, Zhi Qin; Raja Ali, Raja Affend; Shahrani, Shahreedhan; Leow, Alex Hwong-Ruey; Hilmi, Ida Normiha (Frontiers in Medicine, 2022)
Background and Aims Thiopurines, which are immunosuppressive drugs for maintaining remission for inflammatory bowel disease, are known to cause myelotoxicity in patients with Nudix Hydroxylase 15 (NUDT15) genetic variants in some Asian countries with monoethnic populations. We aimed to investigate the association of NUDT15 variants with leukopenia in a multiethnic population in Southeast Asia. Methods Patients with a confirmed diagnosis of inflammatory bowel disease were recruited. We collected demographic and clinical characteristics and whole blood counts before and after initiating thiopurines. Thiopurine S-methyltransferase (TPMT) and NUDT15 genotypes were analyzed with the single nucleotide polymorphisms (SNPs) genotyping assay. Leukopenia was defined as a white blood cell (WBC) count < 3,000/μl. Results In this study, 19 (18.6%) of the 102 patients who had adequate thiopurine therapy experienced leukopenia, 11 patients (57.9%) had NUDT15 c.415C > T variants, 2 patients (10.5%) had NUDT15 c.52G > A variants while one (5.3%) had a TPMT variation. Individually, NUDT15 c.415C > T had a sensitivity and specificity of 57.9% and 94.0% (odds ratio [OR] = 21.45, 95% CI 5.94–77.41, p < 0.001), respectively, for predicting thiopurine-induced leukopenia, while NUDT15 c.52G > A was only observed in patients with leukopenia. As compared with patients with wild-type NUDT15, both NUDT15 variations had a combined sensitivity and specificity of 68.4% and 94%, respectively (OR = 33.80, 95% CI 8.99–127.05, p < 0.001), for predicting thiopurine-induced leukopenia as well as a shorter onset to leukopenia (median onset [months] 2.0 vs. 5.5; p = 0.045). Sub-group analysis showed that both NUDT15 variations were strongly associated with leukopenia among the Chinese and Indians but not among the Malays. Conclusion Nudix Hydroxylase 15 variants strongly predicted thiopurine-induced leukopenia across a multiethnic Southeast Asian population, particularly among the Chinese and Indians.